2018
DOI: 10.3389/fpsyg.2018.01653
|View full text |Cite
|
Sign up to set email alerts
|

Why the Cells Look Like That – The Influence of Learning With Emotional Design and Elaborative Interrogations

Abstract: We investigated emotional design features that may influence multimedia learning with a self-generated learning (SGL) activity, namely answering elaborative interrogations. We assumed that a positive emotional design would be associated with a higher motivation to accomplish the additional SGL activity. Moreover, an interaction was expected: Learners learning with a positive emotional design should profit from learning with elaborative interrogations whereas learners learning with a negative emotional design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 48 publications
(69 reference statements)
3
15
1
Order By: Relevance
“…Regarding the motivational outcome, no positive effect of visual emotional design on motivation was found in the present study (a lack support of H3), which was not consistent with some of the previous studies (e.g., Gong et al, 2017a;Navratil et al, 2018). It could be interpreted as the motivation decreasing function of the learning material itself (Knörzer et al, 2016;Stark et al, 2018a).…”
Section: Brief Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding the motivational outcome, no positive effect of visual emotional design on motivation was found in the present study (a lack support of H3), which was not consistent with some of the previous studies (e.g., Gong et al, 2017a;Navratil et al, 2018). It could be interpreted as the motivation decreasing function of the learning material itself (Knörzer et al, 2016;Stark et al, 2018a).…”
Section: Brief Discussioncontrasting
confidence: 99%
“…Emotional design was defined as the use of different design features with the goal of impacting learners' emotions as a way to enhance learning (Park et al, 2015b). One thing should be noted that emotional design is the design of the intrinsic learning content and should not impose additional information on the learning topic (Navratil et al, 2018).…”
Section: Emotional Design In Multimedia Learningmentioning
confidence: 99%
“…According to color psychology, the feeling of people is stimulated by warm colors whereas cool colors induce a sense of relaxation and calming effect (Elliot and Maier, 2014). Besides that, color heightened motivation on the learner to continue learning from the materials as the color might be perceived as more vivid and interesting (Navratil et al, 2018). Our experiment shows that colored MLMs are able to induce positive emotion on participants while a similar finding was reported by Um et al (2007), Um et al (2012), Mayer and Estrella (2014), Le et al (2018), Münchow and Bannert (2018), Navratil et al (2018), and Uzun and Yıldırım (2018); which confirmed the effect of color on emotional experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, color heightened motivation on the learner to continue learning from the materials as the color might be perceived as more vivid and interesting (Navratil et al, 2018). Our experiment shows that colored MLMs are able to induce positive emotion on participants while a similar finding was reported by Um et al (2007), Um et al (2012), Mayer and Estrella (2014), Le et al (2018), Münchow and Bannert (2018), Navratil et al (2018), and Uzun and Yıldırım (2018); which confirmed the effect of color on emotional experiences. Positive emotion strengthens motivation, attention and behavioral intentions that facilitate learning and enhance memory (Pekrun, 1992) as hypothesized by the Broaden-and-Build theory (Fredrickson, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Third, in our knowledge test we used open-ended questions, consisting of a free-recall test (retention) and a transfer test. However, there are surprisingly few studies concerning elaborative interrogation that assessed knowledge by means of open answer formats, and even fewer studies used measures of comprehension and transfer (e.g., McDaniel and Donnelly, 1996; Dornisch and Sperling, 2006; Dornisch et al, 2011; Roelle et al, 2015; Navratil et al, 2018). Overall, the results of these studies concerning the impact of elaborative interrogation on learning outcomes are not that positive, but rather mixed (for an overview see Dunlosky et al, 2013).…”
Section: Discussionmentioning
confidence: 99%